THE RELATIONSHIP OF THE MENSTRUAL CYCLE, MENSTRUAL LENGTH, FREQUENCY OF MENSTRUATION, AND PHYSICAL ACTIVITIES WITH THE INCIDENT OF ANEMIA IN ADOLESCENTS GIRLS AT ISLAMIC BOARDING SCHOOL - pibriyanti, kartika; Nufus, Nuril Tazkiyatun; Luthfiya, Lulu' (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2021)
Background: Currently anemia is still a health problem. One of the causes of anemia is bleeding that occurs during menstruation. Menstrual disorders can be influenced by body weight, frequency of exercise, physical activity, diet, environmental exposure. Women with long menstrual periods cause more blood to flow, which can lead to anemia.Objectives: This study aims to determine the relationship between menstrual cycles, menstrual length, menstrual frequency, and physical activity with the incidence of anemia in adolescent girls in Islamic boarding schools.Methods: This study used an observational analytic method with a case-control approach. The calculation of the formula used hypothesis test for an odds ratio, obtained a total sample of 84 people. The sampling technique was quota sampling who met the inclusion criteria.Univariate analysis was analyzed using descriptive statistical tests. Bivariate analysis was analyzed using Chi Square and Fisher Exact Test that Â was carried out to determine the relationship between each independent variable and the dependent variable. The research instrument for variable menstrual cycle, menstrual length, and frequency of menstruation used questionnaires that used adolescents as respondents, while for variables of physical activity using an international physical activity questionnaire (IPAQ). Blood collection to determine anemia levels using a hemocue tool (easy touch).ResultsThe results showed the factors associated with anemia were menstrual cycle (p = 0.024; OR = 5.45), menstrual length(p = 0.026; OR = 8.2), and frequency of menstruation (p = 0.026; OR = 2.16), while the unrelated factor was physical activity.Conclusion: Menstrual cycle, menstrual length, and frequency of menstruation is a factor affecting anemia, while physical activity is not a factor affecting anemia.